Mastering the Currency Market: Forex Strategies for High and Low Volatility Markets - Norris Jay (MC Graw Hill, 2010)
Mastering the Currency Market is a comprehensive guide to currency and futures trading strategies and techniques for both highly volatile and nonvolatile markets.